2012
DOI: 10.1007/s00381-012-1922-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea in syndromic craniosynostosis occurs independent of hindbrain herniation

Abstract: Sleep apnoea in syndromic craniosynostosis is not caused by HH. Rather, our evidence suggests that sleep-disordered breathing in craniosynostosis may be caused by brain stem immaturity in young children or upper airway obstruction. Therefore, as long as the child remains asymptomatic, our preferred management of HH is to be conservative and provide regular neurosurgical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Indeed, only 2 of these patients had central apneas outside the normal range (26). Similar findings have also been described in a separate study where sleep study parameters, including both the CAI and OAHI of craniosynostosis patients with hind brain herniation were similar to those without hind brain herniation (27). …”
Section: Cranosynostosis and Central Apneassupporting
confidence: 87%
“…Indeed, only 2 of these patients had central apneas outside the normal range (26). Similar findings have also been described in a separate study where sleep study parameters, including both the CAI and OAHI of craniosynostosis patients with hind brain herniation were similar to those without hind brain herniation (27). …”
Section: Cranosynostosis and Central Apneassupporting
confidence: 87%
“…Horizontal lines indicate the different severity levels of pediatric OSA: mild OSA AHI 1-4.9, moderate OSA AHI 5.0-9.9, and severe OSA AHI ≥ 10. morphology of the upper airway from birth, predisposing to sleep disordered breathing symptoms and OSA. [7][8][9][10][11] Nevertheless, we found that even in "mild" non-syndromic CFM where the pharyngeal airway may not be involved, such as in isolated cleft lip, the presence of symptoms was associated with a frequency of OSA greater than 90%. It has been previously reported that children with syndromes are more likely to have symptoms and undergo PSG.…”
Section: Discussionmentioning
confidence: 71%
“…[7][8][9] However, only two studies have prospectively investigated the frequency of OSA in children with CFM. The fi rst one was conducted in children with syndromic craniosynosotosis 10 and the second in 50 infants with cleft lip and/or palate prior to any surgical procedure. 11 While these previous studies support an association between CFM and pediatric OSA, available data are limited to children with a specifi c CFM or to children in a particular age range.…”
mentioning
confidence: 99%
“…The most widely accepted operative window is within 1 year of age to get maximum benefits in terms of IQ and cognition, with many authors favouring surgery between 6 and 12 months [4,[15][16][17]. Fifty two percentage of our cases were operated in this desirable period.…”
Section: Discussionmentioning
confidence: 93%